2005
DOI: 10.2486/indhealth.43.89
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related Risk of Occupational Injuries in Japanese Small and Medium-scale Enterprises

Abstract: A cross-sectional study evaluated the contribution of daily sleep habits to occupational injuries. A self-administered questionnaire solicited answers about sleep, symptoms of depression, occupational injury, demographics, presence of diseases and lifestyle factors from 2,903 workers between the ages of 16-83 (mean 45) yr in small and medium-scale enterprises. Eight sleep habits were queried and dichotomized: 1) less or more than 6 hr of daily sleep, 2) taking more or less than 30 min to fall asleep (Difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 42 publications
3
61
2
Order By: Relevance
“…In previous research, untreated mood disorder can impair cognitive function and increase accident proneness (Dewa et al 2007). Fatigue (Swaen et al 2003) and sleeping health (Nakata et al 2005) also aVect the occurrence of occupational injuries. Second, the depression causes occupational injury through the adverse eVects of depression treatment, including fatigue, sleeping disturbance, and cognitive impairment (Gilmore et al 1996;Simpson et al 2005;Wadsworth et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, untreated mood disorder can impair cognitive function and increase accident proneness (Dewa et al 2007). Fatigue (Swaen et al 2003) and sleeping health (Nakata et al 2005) also aVect the occurrence of occupational injuries. Second, the depression causes occupational injury through the adverse eVects of depression treatment, including fatigue, sleeping disturbance, and cognitive impairment (Gilmore et al 1996;Simpson et al 2005;Wadsworth et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The difference observed between the higher risk of accidents at work and the lower risk at the wheel could be explained by the more monotonous conditions at work, which could promote inattention and accidents. In a population of small-and medium-sized enterprises, Nakata et al 89) (in this issue) found that workers with trouble falling asleep, sleeping poorly at night, insufficient sleep, and insomnia symptoms had higher occupational injury rate than workers without these sleep features.…”
Section: Work Accidentsmentioning
confidence: 99%
“…The studies on direct costs have been made only in two countries 81,89) and it is difficult to apply these results to other parts of the world. The studies on indirect costs are based on hypotheses which have still restricted bases and have to be confirmed by larger studies in more representative samples.…”
Section: Indirect Costs Of Insomniamentioning
confidence: 99%
“…Based on previous epidemiological studies of sleep 1,2,25,26) , 8 self-reported questions related to sleep problems were selected for this study, namely, (1) difficulty initiating sleep (DIS), (2) difficulty maintaining sleep (DMS), (3) early morning awakening (EMA), (4) dozing off or napping in daytime, (5) insufficiency of sleep, (6) excessive daytime sleepiness (EDS) at work, (7) difficulty awakening in the morning (DAM), and (8) tiredness upon awakening in the morning. Each sleep question was dichotomized, and a criterion response was set (see Table 1).…”
Section: Sleep Problemsmentioning
confidence: 99%
“…Poor sleep is prevalent in modern industrialized society 1,2) , and its consequences include functional impairments, reduced quality of life, and significant health care costs 3) . Moreover, among the working population, sleep problems are associated not only with deteriorated health (e.g., psychological distress, physical complaints), but also with poor work functioning, which can result in increased risk of accidents or injuries at work, absenteeism, reduced productivity, and job dissatisfaction 1,4) .…”
Section: Introductionmentioning
confidence: 99%